2019
DOI: 10.1108/jibr-06-2018-0163
|View full text |Cite
|
Sign up to set email alerts
|

Psychological empowerment and stress: role of personality and power distance

Abstract: Purpose The negative links between psychological empowerment (PE) and perceived stress may be arguable when evaluated in Indian work settings characterized by socio-cultural values like dependence proneness and high power distance. To explore this possibility, the present study aimed to examine the links between PE at work and perceived stress in the Indian milieu. Potential moderating effects of gender, personality (generalized self-efficacy and Big-5 traits) and power distance on this relationship were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…There is an ongoing debate about the effects of empowerment on the level of stress experienced by employees [59,62]. According to Tripathi and Bharadwaja [94], PE may cause high feelings of strain. When perceived autonomy is too high, employees might experience a lack of direction or excessive responsibility, causing them to experience stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing debate about the effects of empowerment on the level of stress experienced by employees [59,62]. According to Tripathi and Bharadwaja [94], PE may cause high feelings of strain. When perceived autonomy is too high, employees might experience a lack of direction or excessive responsibility, causing them to experience stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Chung [93], PE had an inverse moderate correlation with job stress and a moderate correlation with job satisfaction. The results obtained by Tripathi and Bharadwaja [94] showed that PE was negatively related to perceived stress in a non-Western context (India) and using experimental methodology. In the meta-analytic review carried out by Seibert et al [59], PE was positively associated with job satisfaction and negatively with employee strain, among other results.…”
Section: Empowerment Health and Well-beingmentioning
confidence: 96%
“…A recently conducted study on 23,468 employees in the European Union found that psychological empowerment is positively associated with job satisfaction, work engagement and social well-being (Martin-Garcia and Bonavia, 2021). In a study conducted in the Indian context, Tripathi and Bharadwaja (2019), psychological empowerment is negatively related to job stress. It is expected that when employees feel less stress at work, performance is likely to decrease.…”
Section: Empowerment and Performancementioning
confidence: 98%
“…Sources of work stress can also come from physical and physical threats and violence at work (Allison et al, 2019;Rasool et al, 2020), financial problems (Kongcharoen et al, 2019), delays in information (Ajayi et al, 2019), the use of digital technology (Rafida, 2020), countermeasures, resilience extraversion, awareness and neuroticism (Duschek et al, 2019), personal relationships outside of work and lack of free time for family and friends (Galanis et al, 2018), customer misbehaviors (Hu et al, 2017), customer abusive behaviour (Kashif et al, 2017) psychological empowerment (Tripathi and Bharadwaja, 2018) and spirituality at work (Saxena et al, 2020). Some of the antecedent variables of work stress have never been studied in previous studies, thus adding to the research literature on work stress.…”
Section: Antecedents Of Work Stressmentioning
confidence: 99%
“…Research in the literature observed by the authors shows that work stress is studied in various types of work. Observations show that research on work stress is carried out in the construction professional profession (Ajayi et al, 2019;Hampton et al, 2019;Naoum et al, 2018), the police (Allison et al, 2019;Li et al, 2018;Nisar and Rasheed, 2019), teachers and headmaster (Heyder, 2019;Hu et al, 2019;Kongcharoen et al, 2019;Walker, 2020), Paramedics (Bjaalid, 2020;Duschek et al, 2019;Klein et al, 2019;Manoppo, 2020;Park et al, 2020;Rasool et al, 2020;Saadeh and Suifan, 2020;Zaghini et al, 2020), hotel industry employees (Goswani et al, 2019;Yousaf et al, 2020) and banking industry employees (Darte-Baah, 2019;Kashif et al, 2017;Oruh et al, 2020;Pandey, 2020;Parveen and Adeinat, 2019;Tripathi and Bharadwaja, 2018;Wu, 2020;). Some professions are only studied by one researcher, for example in the profession of daycare leader (Elomaa et al, 2020), library staff (Petek, 2018), the salesperson (Peaslay et al, 2020), women micro-entrepreneurs (Wijewardena et al., 2020), auditors (Amirudin, 2019), immigration officers (Yang et al, 2019), employees in the electricity sector (Sidhu et al, 2020), lecturers (Rafida, 2020), cabin crewmembers…”
Section: Types Of Work Researched In Research On Work Stressmentioning
confidence: 99%